Evaluation of retinal nerve fiber layer thickness measurements using optical coherence tomography in patients with tobacco-alcohol-induced toxic optic neuropathy - Moura, Frederico C (Medknow Publications, 2010)
Three patients with progressive visual loss, chronic alcoholism and tabagism were submitted to a complete neuro-ophthalmic examination and to retinal nerve fiber layer (RNFL) measurements using optical coherence tomography (OCT) scanning. Two patients showed marked RNFL loss in the temporal sector of the optic disc. However, a third patient presented RNFL measurements within or above normal limits, based on the Stratus-OCT normative database. Such findings may be due to possible RNFL edema similar to the one that may occur in the acute phase of toxic optic neuropathies. Stratus-OCT was able to detect RNFL loss in the papillomacular bundle of patients with tobacco-alcohol-induced toxic optic neuropathy. However, interpretation must be careful when OCT does not show abnormality in order to prevent diagnostic confusion, since overestimation of RNFL thickness measurements is possible in such cases.